Stability analysis for economic traits and infestation of melon fruit-fly (Dacus cucurbitae) in bittergourd (Monordica charantia) - THAKUR, J C; KHATTRA, A S; BRAR, K S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1989-91 to study stability of 10 cultivars of bittergourd (Momordica charantia L.) for economic traits.'Punjab 14' gave higher total (23.09 tonnes/ha) andmarketable yield (20.33 tonnes/ha) and proved most stable for days taken to first harvest, days for 50% harvest and fruit weight. It also proved stable for total and marketable yield under favourable conditions. 'C 96' was most stable for fruits/plant and infestation by melon fruit-fly (Dacus cucurbitae Coq.) andÂ  'NDBT 1 was most stable for fruit-fly infestation only.